Gloria's way - Cameron, Ann, 1943-; Toft, Lis. (New York : Scholastic, Inc., 2000)
Gloria shares special times with her mother and father and with her friends Julian, Huey, and Latisha.(Gr.3-5)
410
Accelerated Reader AR
Keywords: Friendship -- Fiction; Parent and child -- Fiction; African Americans -- Fiction